2020
DOI: 10.1111/gcb.15430
|View full text |Cite
|
Sign up to set email alerts
|

Divergent drivers of the microbial methane sink in temperate forest and grassland soils

Abstract: Aerated topsoils are important sinks for atmospheric methane (CH4) via oxidation by CH4‐oxidizing bacteria (MOB). However, intensified management of grasslands and forests may reduce the CH4 sink capacity of soils. We investigated the influence of grassland land‐use intensity (150 sites) and forest management type (149 sites) on potential atmospheric CH4 oxidation rates (PMORs) and the abundance and diversity of MOB (with qPCR) in topsoils of three temperate regions in Germany. PMORs measurements in microcosms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 92 publications
6
48
0
Order By: Relevance
“…Additionally, of USCα methanotrophs which are characterized by pmoA genes that distantly cluster from known methanotrophs 51 , 52 a draft genome has been recovered from forest soils via metagenomics sequencing methods and shedded light on CH 4 metabolic potential and environmental adaptions 53 . The derived high affinity for CH 4 and potential to oxidize atmospheric CH 4 concentrations was especially proposed for upland soils, mainly for acidic soils 12 , 15 , 16 , making USCα a major biological sink of CH 4 in forest soils 54 , 55 . Furthermore, methanotrophic Beijerinckiaceae strains to which members of the USCα belong were mostly isolated from peatlands or forest soils 12 .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, of USCα methanotrophs which are characterized by pmoA genes that distantly cluster from known methanotrophs 51 , 52 a draft genome has been recovered from forest soils via metagenomics sequencing methods and shedded light on CH 4 metabolic potential and environmental adaptions 53 . The derived high affinity for CH 4 and potential to oxidize atmospheric CH 4 concentrations was especially proposed for upland soils, mainly for acidic soils 12 , 15 , 16 , making USCα a major biological sink of CH 4 in forest soils 54 , 55 . Furthermore, methanotrophic Beijerinckiaceae strains to which members of the USCα belong were mostly isolated from peatlands or forest soils 12 .…”
Section: Discussionmentioning
confidence: 99%
“…Gas concentrations were measured on an Agilent 7890 gas chromatograph equipped with a flame ionization detector (for CH4) coupled with a methanizer (for CO2) (Agilent Technologies Inc., Santa Clara, CA, USA). Gas flux rates were calculated by the slope of the regression line of a linear regression of the gas concentration against time [17].…”
Section: Gas Fluxesmentioning
confidence: 99%
“…However, it is not fully understood which microorganisms oxidize CH4 at atmospheric concentrations in soils. Bacteria of upland soil clusters (USC-α) and USC-γ have been identified as likely important atmospheric CH4 oxidizers in upland soils [12,17,18], while well-known methanotrophic lineages also account for CH4 oxidation in anoxic paddy soils [19].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that the abundance, diversity, and community structure of methanotrophs and methanogens are mainly influenced by soil pH 51,52 , NH 4 + concentration 16 , and soil substrate 53 . For example, pH has a negative effect on upland soil cluster (USC)-α and a positive effect on USC-γ abundance 54 . USC-α has been detected in mostly acidic upland soils 55 , whereas USC-γ is detected in alkaline upland soils 56,57 .…”
mentioning
confidence: 99%
“…USC-α has been detected in mostly acidic upland soils 55 , whereas USC-γ is detected in alkaline upland soils 56,57 . Furthermore, few studies have linked CH 4 fluxes to the abundances of methanotrophs and methanogens and the environmental factors influencing their abundances 54 . Thus, it is equally important to investigate N deposition on the relationship between soil CH 4 flux and the abundance and community structure of the methanotrophs and methanogens in Moso bamboo forests.…”
mentioning
confidence: 99%